Peranan Pembelajaran Metafora dalam Meningkatkan Prestasi Belajar Matematika Peserta didik - Nova Fitria Ningsih; Yurnalis Yurnalis (Lattice Journal : Journal of Mathematics Education and Applied, 2022)
Metaphor learning is learning that changes abstract mathematical concepts into concrete through actions that connect concepts with pre-existing material and with everyday life. The role of metaphor learning can improve students' mathematics learning achievement. The purpose of this study is to describe the learning of metaphors in improving students' mathematics learning achievement. This research is library research, which is digging information from previous findings regarding the role of metaphor learning in improving students' mathematics learning achievement in the study of literature. Data collection technique in this research is documentation technique. Sources of data used in the form of primary and supporting data sources derived from previous research. Based on the results of research that has been carried out, there are several roles of metaphor learning in improving students' mathematics learning achievement, namely metaphorical learning (1) can change abstract mathematical concepts into concrete through activities connecting concepts with previous material and real life, (2) can improve reasoning abilities students, (3) can encourage students to learn and make students interested in mathematics, (4) indirectly students experience the process of thinking metaphorically through the CREATE stages (Connect, Relate, Explore, Analyze, Transform, and Experience).Pembelajaran metafora merupakan pembelajaran yang mengubah konsep matematika yang bersifat abstrak menjadi konkrit melalui kegiatan menghubungkan konsep dengan materi yang sudah diketahui sebelumnya dan dengan kehidupan sehari-hari. Peranan pembelajaran metafora dapat meningkatkan prestasi belajar matematika peserta didik. Adapun tujuan penelitian ini adalah untuk mendeskripsikan peranan pembelajaran metafora dalam meningkatkan prestasi belajar matematika peserta didik. Penelitian ini adalah penelitian kepustakaan (library research) yaitu menggali informasi dari temuan sebelumnya mengenai peranan pembelajaran dengan metafora dalam meningkatkan prestasi belajar matematika peserta didik di dalam studi literatur. Teknik pengumpulan data dalam penelitian ini adalah teknik dokumentasi. Sumber data yang digunakan berupa sumber data utama dan pendukung yang berasal dari penelitian sebelumnya. Berdasarkan hasil temuan penelitian yang telah dilakukan, terdapat beberapa peranan pembelajaran metafora dalam meningkatkan prestasi belajar matematika peserta didik yaitu pembelajaran metafora (1) dapat mengubah konsep matematika yang abstrak menjadi konkrit melalui kegiatan menghubungkan konsep dengan materi sebelumnya dan kehidupan nyata, (2) dapat meningkatkan kemampuan penalaran matematis peserta didik, (3) dapat memberikan semangat kepada peserta didik untuk belajar dan membuat peserta didik tertarik terhadap matematika, (4) secara tidak langsung peserta didik mengalami proses berpikir metafora melalui tahapan CREATE (Connect, Relate, Explore, Analyze, Transform, dan Experience).